2012
DOI: 10.1021/tx3002884
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Toxicity of Amorphous Silica Nanoparticles on Human Lung Submucosal Cells in Vitro: Protective Effects of Fisetin

Abstract: There is growing evidence that amorphous silica nanoparticles (SiO₂-NP) can cause an inflammatory response in the lung. We studied in vitro the effects of exposing human lung submucosal cells to SiO₂-NP of various sizes (10, 150, and 500 nm) for 2-24 h. Cell survival, reactive oxygen species (ROS), malondialdehyde (MDA) levels, cytokine production, inflammatory gene expression, and genotoxicity were measured after exposure of Calu-3 cells to 10SiO₂-NP in the presence or absence of the flavanoid fisetin and an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(74 citation statements)
references
References 43 publications
(84 reference statements)
3
64
0
Order By: Relevance
“…We have shown an elevation of ROS levels in human gingival fibroblast cells exposed to silver NPs and human lung submucosal cells exposed to silicon dioxide NPs. 17,39 Moreover, it has been reported that nanoscale TiO 2 could be phagocytized by neurons and microglia, which then release ROS: OH and O 2…”
Section: Titanium Dioxide Nanoparticles Induce Generation Of the Supementioning
confidence: 99%
“…We have shown an elevation of ROS levels in human gingival fibroblast cells exposed to silver NPs and human lung submucosal cells exposed to silicon dioxide NPs. 17,39 Moreover, it has been reported that nanoscale TiO 2 could be phagocytized by neurons and microglia, which then release ROS: OH and O 2…”
Section: Titanium Dioxide Nanoparticles Induce Generation Of the Supementioning
confidence: 99%
“…[5][6][7] The presence of nanoparticles induces oxidative stress and inflammation and affects degradation pathways with an appearance of autophagosomes and lysosomal dysfunctions, leading to autophagy and apoptosis. [8][9][10] At biocompatible doses, their ability to easily enter the cell has been proposed as an asset for drug delivery, [11][12][13] cell tracking, and cell therapy, 14,15 with a particular focus on the delivery of anticancer therapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…These adverse effects could be mediated by oxidative stress or/and the activation of stress-related signalling pathways [21,22]. The toxicity appears to be dependent on NP size and surface [17,[23][24][25][26]. For instance, Li et al have demonstrated that SiO 2 NP with diameters of 19, 43, 68 and 498 nm cause cytotoxicity, increased reactive oxygen species (ROS) level, DNA damage and cell cycle arrest in HepG2 cells in a size-dependent manner [23].…”
Section: Introductionmentioning
confidence: 99%